171k views
5 votes
5-(m-4)= 2m+ 3 (m-1)

User Parijat
by
5.8k points

1 Answer

2 votes

Answer: m= 2

Step-by-step explanation: First Expand the brackets! 5-m+4=2m+3m-3

Then Do the addition and subtraction in both sides!

9-m=5m-3

Then bring m to one side and the constants the other!

6m=12

Then solve for m where m=2

If you want you can check your answer bu substituting m as 2. 5-(2-4)=7 and 2(2) + 3(2-1) which also = 7.

User Logancautrell
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.